2022
DOI: 10.1212/nxi.0000000000001153
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Opsoclonus-Myoclonus-Ataxia Syndrome in Children

Abstract: Background and ObjectivesOpsoclonus-myoclonus-ataxia syndrome (OMAS) is a rare disorder of the nervous system that classically presents with a combination of characteristic eye movement disorder and myoclonus, in addition to ataxia, irritability, and sleep disturbance. There is good evidence that OMAS is an immune-mediated condition that may be paraneoplastic in the context of neuroblastoma. This syndrome may be associated with long-term cognitive impairment, yet it remains unclear how this is influenced by di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 64 publications
1
68
0
6
Order By: Relevance
“…Recent studies have suggested utility of rituximab based on the expansion of cerebrospinal fluid B cells in the pathogenesis of OMAS. 3 9 In our study, two children needed rituximab as there was ill-sustained response to steroids and IVIG. However, due to lack of improvement one child (subject 6) was started on pulse dexamethasone and cyclophosphamide monthly for four cycles after which he became ambulatory.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Recent studies have suggested utility of rituximab based on the expansion of cerebrospinal fluid B cells in the pathogenesis of OMAS. 3 9 In our study, two children needed rituximab as there was ill-sustained response to steroids and IVIG. However, due to lack of improvement one child (subject 6) was started on pulse dexamethasone and cyclophosphamide monthly for four cycles after which he became ambulatory.…”
Section: Discussionmentioning
confidence: 75%
“…This has been noted previously and attributed to low grade of the tumor. 3 6 7 This observation is particularly relevant in low- and middle-income countries where cost and availability of MIBG scan and urinary VMA is a constraint. These are likely to add to delay in diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations